Development of Pandeglang Local History Teaching Media in Increasing High School Students' Historical Awareness - Herdin Muhtarom; Andi Andi (Yupa: Historical Studies Journal, 2023)
The development of technology-based teaching media in history aims to improve the quality of education by utilizing technology and enhancing historical awareness. The utilization of the Pandeglang Local History learning media holds excellent appeal for incorporating local history into the learning process. The innovative use of the Local History application further elucidates how technology can enhance historical awareness in the context of local history education. This study aims to develop teaching media based on local content to enhance students' historical awareness through technological advancements. The research approach employed in this study is Research and Development (R&D), explicitly using the 4D research development model (Define, Design, Develop, Disseminate). The results demonstrated that using local history teaching media, as assessed through the Likert scale validation test, increased high school students' historical awareness. These findings are based on the results of the validation test, which included the design validation test of the Local History application, revealing a score of 100. Subsequently, the application teaching media test yielded a score of 100. Finally, the effectiveness of the Local History application was evaluated, resulting in a score of 100, demonstrating the success of the application's development